Sports practice, walking and biking are positively related to quality of life in adults: A cross-sectional study - Silva, Stefany Carolaine Bezerra [UNESP]; Tebar, William Rodrigues; Ferrari, Gerson; Lemes, Ítalo Ribeiro; Aguilar, Beatriz Anizia Santos [UNESP]; Teixeira, Milena S. [UNESP]; Mota, Jorge; Ritti-Dias, Raphael Mendes; Beretta, Victor Spiandor [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (Elsevier, 2023)
Introduction: Physical activity (PA) has been associated with better quality of life (QoL). However, it is not clear whether this association is similar considering the different PA domains and independent of the intensity of PA practiced. Objective: To analyze the relationship between the time spent in PA in different domains [i.e., occupational, sports practice, walking and biking (through a combination of leisure and active transport)] and the QoL (i.e., physical functioning, role-physical, body pain, general health status, vitality, social functioning, role-emotional, and mental health) in adults. Methods: Two hundred and sixty-one adults with median age of 43.0 years (Interquartile range = 27.0–55.0 years) participated in this epidemiological study with a cross-sectional design. The sample included 261 adults QoL, PA domains, and PA intensities were assessed by the Short-Form Health Survey questionnaire (SF-36), the Baecke questionnaire, and using an accelerometer, respectively. Linear regressions adjusting for sex, age, socioeconomic status, body mass index, smoking status, alcohol consumption, and moderate to vigorous PA were used for analysis. Results: Occupational PA was negatively related to body pain domain of QoL (β = −4.29; 95%CI = −7.27/-1.31). Sports practice was positively related to physical functioning (β = 3.34 95%CI = 0.52/6.15), general health status (β = 5.48; 95%CI = 2.20/8.76), vitality (β = 5.39; 95%CI = 2.18/8.60), and mental health (β = 3.47; 95%CI = 0.27/6.67) domains of QoL. Walking and biking were positively associated with vitality (β = 4.48; 95%CI = 0.84/8.13) and mental health (β = 4.21; 95%CI = 0.64/7.79) QoL domains. Conclusion: In conclusion, PA domains were associated with QoL differently. Regardless of PA intensity (measured objectively) and other factors, walking and biking were associated with indicators of mental health and vitality.
Keywords: Mental health; Physical activity domains; Physical activity intensities; Physical exercise; Public health